Mitigating High-risk EBV and CMV Through Kidney Paired Donation: A Survey of Potential Donor and Recipient Candidates - Arjun Kalaria, MD; Rajil B. Mehta, MD; Puneet Sood, MD, MPH; Xingyu Zhang, PhD; Harry J. Morford, BS; Vishnu Potluri, MD, MPH; John F. P. Bridges, PhD; Chethan M. Puttarajappa, MD, MS (Transplantation Direct)
Background. High-risk cytomegalovirus (CMV) and Epstein-Barr virus (EBV) mismatches (ie, seropositive donors to seronegative recipients) among kidney transplant recipients lead to increased healthcare utilization, inferior allograft outcomes, and high mortality. We assessed the interest among prospective kidney donor and recipient candidates to participate in kidney paired donation (KPD) for averting CMV/EBV high-risk mismatches. Methods. We surveyed 51 potential living donors and 102 kidney recipient candidates presenting for their evaluation visit at the University of Pittsburgh Medical Center between October 2022 and May 2023. We evaluated their general inclination toward KPD and their interest in KPD under various risk-benefit scenarios, particularly emphasizing the mitigation of high-risk mismatches associated with EBV and CMV. This was done using a 5-point Likert scale (1-low interest; 5-high interest) customized survey. Results. There was high interest in KPD among both donor and recipient candidates (median score 4 versus 4; P = 0.09). However, donor candidates had a lower interest in KPD if they were compatible with their intended recipient (median score 2 versus 4; P < 0.001). Most donor (80.4%; N = 41) and recipient candidates (89.2%; N = 91) expressed a strong willingness to participate in KPD to prevent high-risk CMV and EBV mismatches, but this interest declined with longer transplant delays. Interest also varied on the basis of participants’ income and employment status. Conclusions. Interest in KPD for avoiding CMV and EBV was high among both donor and recipient candidates. Additional research is required to assess the capacity and desirability for KPD expansion, particularly among ABO and HLA-compatible pairs.